Next generation sequencing approaches for the detection and characterization of enteroviruses in clinical, public health, and research settings: Expert view of the European non-polio enterovirus network (ENPEN) - Benschop, Kimberley S. M.; Zwagemaker, Florian; Andersson-Li, Lili; Andrés, Cristina; Antón, Andrés; Berengua, Carla; Berginc, Natasa; Bessaud, Maël; Bisseux, Maxime; Bujaki, Erika; Canning, Benjamin; Christiansen, Claus Bohn; et al. (Elsevier, 2026)
Enteroviruses (EVs) are a common cause of a wide spectrum of infectious diseases, ranging from mild respiratory illnesses to severe neurological conditions, particularly affecting children. Current molecular methods, such as 5′UTR-based PCR for detection and (partial) VP1 gene sequencing for typing, are widely utilized. However, Next-Generation Sequencing (NGS), and bioinformatics offer a comprehensive alternative, enabling full-genome analyses for improved virus characterization, genomic epidemiological surveillance, and outbreak investigation. Despite its advantages, implementation of NGS poses challenges, particularly in standardizing and optimizing laboratory workflows (wet-lab) and bioinformatics analyses (dry-lab), methods that are not often readily accessible in many laboratories. Here, we discuss the potential of NGS as a tool for EV detection/characterization in clinical virology, public health, and research settings. We provide practical options for actions for implementing NGS to advance the understanding and management of enterovirus infections. These recommendations are based on expert discussions during the recent European non-polio enterovirus network (ENPEN) workshop held in Corfu, Greece, on 23–24 May 2024, aiming to guide harmonization of NGS practices across clinical, public health, and research settings.